Stability Enhancement of Iron‐based Perovskite Catalysts by A‐site Substitution for Oxidative Transposition of α‐Bromostyrene to Phenacyl Bromide. Issue 18 (7th July 2022) - Shibata, Satomi; Kamata, Keigo; Hara, Michikazu
Abstract: LaFeO3 nanoparticles, which were synthesized by the sol‐gel method using aspartic acid, acted as efficient and stable heterogeneous catalysts for the oxidative transformation of α‐bromostyrene to phenacyl bromide using only air under mild conditions without the need for additives and light irradiation. The stability of Fe‐containing perovskite oxides was significantly improved by changing the A‐site metal cation from alkaline metals to lanthanum. LaFeO3 showed much higher catalytic activities than other Fe 3+ /Fe 2+ ‐containing simple oxides. Mechanistic studies showed the involvement of a radical‐type mechanism involving surface adsorbed O2 species over p‐type LaFeO3 . Such an active oxygen species was applicable to the aerobic oxidative cleavage of 1, 1‐diphenylethylene and oxidative coupling of p ‐toluenethiol. Abstract : Perovskite : LaFeO3 nanoparticles, which was synthesized by the sol−gel method using aspartic acid, acted as an efficient and stable heterogeneous catalyst for the aerobic oxidative transformation of α‐bromostyrene to phenacyl bromide without the need for additives and light irradiation. The stability of Fe‐containing perovskite oxides was significantly improved by changing the A‐site metal cation from alkaline metals to lanthanum.